Review paperNew aspects of the treatment of alopecia areata - Brzezińska-Wcisło, Ligia; Bergler-Czop, Beata; Wcisło-Dziadecka, Dominika; Lis-Święty, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Alopecia areata (AA) is a disease involving non-scarring hair loss determined by autoimmune disorders and inflammation. The disease affects hair on the scalp and/or other parts of the body. The AA occurs in people of all ages and affects 1–2% of humans. The purpose of this paper is to present the latest knowledge on the treatment of AA. The decision on the type of treatment depends on the type of hair loss, extent of changes, general health status, the patient’s age, and his/her motivation. Treatment methods should be chosen individually for each patient.